The Extended Simple View of Reading in Adult Learners of Chinese as a Second Language - Hao, Meiling; Fang, Xiaoping; Sun, Zhenzhen; Liu, Youyi (Frontiers in Psychology, 2022)
The Simple View of Reading (SVR) designates that reading comprehension is the product of decoding and listening comprehension and this conclusion has been supported by studies on school-aged native and nonnative speakers. However, it remains unknown whether SVR can be applied to adult second language (L2) learners. The current study addressed this issue by testing adult Chinese L2 learners of various proficiency levels and further extended the model by including word segmentation and word-meaning access, both of which are particularly crucial in reading Chinese. The results showed that listening comprehension only contributed to reading comprehension for the advanced learners, while decoding accuracy predicted reading comprehension regardless of Chinese proficiency. However, the total proportion of variance accounted for was relatively low, especially for the lower proficiency groups. Interestingly, word segmentation and word-meaning access explained a large proportion of the total variance and concomitantly decreased the apparent influence of word decoding. Taken together, these findings highlight that the individual characteristics of a given language can modulate the contributions of decoding and listening comprehension to predicting reading comprehension.